Case reportPointillist melanotic macules: a new clinical entity? - Tan, Cheng; Zhu, Wen-Yuan (Advances in Dermatology and Allergology/Postępy Dermatologii i Alergologii, 2012)
A Chinese male and his father both presented disseminated, variably-sized and pigmented spots as well as stellate macules in their adulthood. No signs indicated a systemic involvement after extensive evaluation. Skin examination revealed that most macules were stellate or claw-like that differ from each other in shape and size. However, as a whole, these discrete lesions were interspersed regularly. Pathological changes included remarkable basilar layer hyperpigmentation (black eye line sign) without proliferation of the melanocytes. Melanophages were noted in the dermis. We proposed the diagnosis of pointillist melanotic macules, and believe this is a new clinical entity.